2022
DOI: 10.1530/rep-21-0313
|View full text |Cite
|
Sign up to set email alerts
|

Endothelin 2: a key player in ovulation and fertility

Abstract: Ovulation is the fundamental biological process during which an oocyte is expelled from the ovary, and it is an essential step toward establishing pregnancy. Understanding regulatory mechanisms governing the ovulation process is essential for diagnosing and treating causes of infertility, identifying contraceptive targets, and developing novel contraception methods. EDN2 is a 21-amino acid long peptide that is transiently synthesized by granulosa cells of the ovulatory follicle prior to ovulation and plays an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 101 publications
2
9
0
Order By: Relevance
“…The LH-induced ingression of the LH receptor-expressing granulosa cells into the inner half of the mural layer, and the associated changes in cell shape, raised the question of how these cellular events might correlate with LH-induced changes in the shape of the follicle as a whole. Constrictions in the basolateral surface of follicles have been previously observed during or within 2 hours of ovulation, but reports at earlier time points are lacking [2429]. By fixing ovaries before or 6-10 hours after injection of mice with kisspeptin, labelling the basal lamina in ovary cryosections, and imaging equatorial cross-sections of preovulatory follicles, we observed that invaginations of the follicle surface began much earlier than previously reported.…”
Section: Resultssupporting
confidence: 48%
See 4 more Smart Citations
“…The LH-induced ingression of the LH receptor-expressing granulosa cells into the inner half of the mural layer, and the associated changes in cell shape, raised the question of how these cellular events might correlate with LH-induced changes in the shape of the follicle as a whole. Constrictions in the basolateral surface of follicles have been previously observed during or within 2 hours of ovulation, but reports at earlier time points are lacking [2429]. By fixing ovaries before or 6-10 hours after injection of mice with kisspeptin, labelling the basal lamina in ovary cryosections, and imaging equatorial cross-sections of preovulatory follicles, we observed that invaginations of the follicle surface began much earlier than previously reported.…”
Section: Resultssupporting
confidence: 48%
“…Likewise, migration of granulosa cells out of the apical region of the mural granulosa could be imagined to contribute to thinning of the follicle apex. While previous studies have provided evidence for the combined action of extracellular proteases [13,21,27] and endothelin-induced contractions of smooth muscle cells in the theca [29] and theca blood vessels [21] in causing both basolateral invaginations and apical thinning, definitive identification of the cells that are responsible remains uncertain.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations